A phlegmon secondary to retroileal appendicitis: A rare cause of mechanical small bowel obstruction. (November 2017) - Mulla, M; Husain, Najam; Bhadra, Anuttara; Waraich, Naseem; Rastegar, Amir
Abstract : Introduction: Appendicitis is common surgical emergency with a lifetime risk of about 7% and a perforation risk of 17-20%. In young patients diagnosis does not pose a great difficulty and the surgical management is generally good. However in the elderly with varied presentation and a difficult history, the diagnosis can be more challenging. Small bowel obstruction as a result of adhesions from appendicitis has been commonly documented in literature. But mechanical small bowel obstruction caused directly as a result of acute appendicitis is rare. We present one of this rare and interesting presentation of appendicitis. Case description: An 83-year-old gentleman presented to the surgical department with a 4-day vague history of abdominal pain associated with vomiting. He had not opened his bowels for a similar time period and also complained of abdominal distension. The patient had an unremarkable past surgical history, with no prior abdominal surgery. General examination showed he was dehydrated, exhausted and looked unwell. His pulse was 94/min, BP was 120/60mmHg and he was apyrexial. His abdomen was markedly distended but soft and non-tender with sluggish bowel sounds. Abdominal x-Rays showed multiple loops of dilated small bowel suggestive of small bowel obstruction. Initially the patient was managed by intravenous fluid resuscitation, nasogastric tube insertion and urethral catheterisation. An arterial blood gas analysis showed significant metabolic acidosis with raised serum lactate and negative base excess. Routine bloods showed raised urea, creatinine and WCC. Despite rigorous resuscitation the patient's condition deteriorated, hence an emergency laparotomy was performed. At surgery loops of distended small bowel were identified extending proximally from the duodeno-jejunal junction to the distal ileum. At approximately 8cm from the ileo-caecal valve, a small appendix was noticed behind the transition point covered in a phlegmon and surrounding inflammation. A routine appendicectomy was performed and the abdomen was closed after thorough wash out with normal saline. No other abnormality was noticed on laparotomy. Unfortunately the patients died a few days after the operation from pneumonia. Results and Conclusions: Appendicitis is the second most common surgical abdominal pathology in people over 50yrs of age. The diagnosis in this age group is often delayed compared to the younger group due to a variety of reasons including difficult history and atypical and delayed presentation. In our case the cause of mechanical small bowel obstruction was noted to be due to inflamed small appendix and phlegmon lying behind the terminal ileum. Presumably the patient must have developed appendicitis a few days prior to presentation to the hospital. This delay had caused the development of phlegmon in which the appendix was found wrapped causing intestinal obstruction. Mechanical small bowel obstruction is recognized as short-term complication (ileus) and long-term adverse effect due to postoperative adhesion after appendicectomy. In literature, appendicitis as a direct cause of small bowel obstruction has been discussed but without describing the position of the appendix and most cases were secondary to perforated appendices and associated peritonitis. Small bowel obstruction without previous surgery to the abdomen is acute surgical emergency and early judicious intervention is needed to improve the final outcome. This case is unique in its presentation of appendicitis and without any obvious signs making the pre-operative diagnosis difficult.